EXPERIMENTAL STUDY OF FIBER REINFORCED COCONUT SHELL AGGREGATE CONCRETE WITH FLY ASH - Udayakumar, S.; kumar, K.Dinesh (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
Solid wastes has increased many fold causing disposal problems and environmental pollution. It has become common sight to find large dumps of solid waste near every town and villages causing air, land and water pollution. A productive use of large scale wastes such as fly ash, coconut shell, rice husks, furnace slag etc., has become a matter of importance, as there is considerable scope for better management and disposal of the same. The waste materials considered in this work are fly ash, coconut shell. The disposal method proposed is by partially using them in building elements such as reinforced concrete elements and plain concrete elements.In this study, the compressive strength of concrete cubes of size 150 mm was carried out. The cement was replaced by 0% 10%, 20%, 30% of fly ash and add 0%, 0.1%, 0.3% and 0.5% of polypropylene fibre. The optimum percentage was found. The crushed coconut shells as substitutes for conventional coarse aggregate in gradation of 50% and 100%. For these optimum percentages three beams of 1700 X150 X100 mm were cast and tested. Extensive measurements such as material properties, deflection and ultimate load carrying capacity of the beams were done in the study for comparison.The experimental results shows that the ultimate load carrying capacity of coconut shell aggregate beam with fly ash and polypropylene fibre were higher than the control beam. The compressive test and split tensile test indicate that the gain in strength depends on curing time and strength increases gradually with the increase in fly ash and fibre content. It is concluded that a maximum of 50% of coarse aggregate can be replaced by coconut shell without any compromise on strength properties. The aim behind this is to use low cost material like coconut shell and thus taking close to the concept of low cost housing.